2015
DOI: 10.4322/rbcv.2015.364
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence for nematodes of hygiene-sanitary importance in fish from Colares Island and Vigia, Pará, Brasil

Abstract: Zoonotic parasites can infect fish and be a serious threat to human health. The objective of this research was to estimate the prevalence for the main fish-borne zoonotic parasitic diseases of freshwater fish marketed in Colares Island and Vigia, Pará, Brazil. In February, 2012, 85 (40 of Colares and 45 of Vigia) fish were randomly sampled by means of net fishing. Eighty and 76% of fish sampled were parasitized, being silver croacker (Plagioscion squamosissimus), kumakuma (Brachyplatystoma filamentosum), and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The prevalence in their study was around 75% higher than what was found in the present study for Anisakis sp. Rodrigues et al (2015) recorded that the prevalence of Anisakis sp. in the same host was slightly lower (10%) than that of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence in their study was around 75% higher than what was found in the present study for Anisakis sp. Rodrigues et al (2015) recorded that the prevalence of Anisakis sp. in the same host was slightly lower (10%) than that of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The present study expands the occurrence of Anisakis sp. in P. squamosissimus to two additional municipalities in the state of Pará (RODRIGUES et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most fish-borne nematodes found in humans are members of Anisakidae and Gnathostomatidae families, and Capillaria philippinensis of Trichinellidae family (EIRAS et al, 2018). The nematodes of these families are reported as parasites of many species of marine and freshwater fishes, but infection in humans can occur by consuming fishes alive, raw or undercooked (CAVALCANTI et al, 2012;ANDRADE-PORTO et al, 2015;RODRIGUES et al, 2015).…”
Section: Nematodamentioning
confidence: 99%